Innovative hurdle system towards Listeria monocytogenes inactivation in a fermented meat sausage model - high pressure processing assisted by bacteriophage P100 and bacteriocinogenic Pediococcus acidilactici. (October 2021) - Komora, Norton; Maciel, Cláudia; Amaral, Renata A.; Fernandes, Rui; Castro, Sónia Marília; Saraiva, Jorge A.; Teixeira, Paula
Graphical abstract: Highlights: Feasibility of associating phages to bacteriocinogenic LAB proved in fermented food. L. monocytogenes eliminated in fermented sausage model with HHP-LAB-phage system. Synergistic listericidal effect between hurdles demonstrated in a solid matrix. In situ biosynthesis of pediocin PA-1 firstly reported in solid matrix. Abstract: Consumers' quest for healthier, locally produced foods, renders the demand for these products increasingly prominent. The purpose of the present work was to evaluate the impact of a non-thermal multi-hurdle approach, which associated mild high hydrostatic pressure (HHP, 300 MPa), the bacteriophage Listex™ P100, and the pediocin PA-1 producing Pediococcus acidilactici HA 6111-2, as a novel minimal processing towards Listeria monocytogenes eradication in Alheira (a traditional fermented meat sausage from Northern Portugal). The combination of the three hurdles achieved the USDA-FSIS 5 log reduction (in accordance with the standard guidelines for ready-to-eat foods), being the only treatment to elicit the absence of L. monocytogenes immediately following processing ( p  < 0.05). The pair association of HHP with Listex™ P100 was unable to eliminate L. monocytogenes, whilst in the HHP-pediocin PA-1 producing P . acidilactici treated samples the eradication was delayed when compared to the three hurdles combination. In addition to the listericidal effect of the HHP-phage-lactic acid bacterium treatment, no significant differences ( p  > 0.05) in the pH values were observed, and the semi-quantification of the in situ biosynthesized pediocin PA-1 was documented for the first time in a fermented meat sausage model.